IMPROVING STUDENTS’ SPEAKING SKILL BY IMPLEMENTING SELF-TALK STRATEGY AT THE ELEVENTH GRADE STUDENTS OF SMKN 2 MATARAM - Ira Megawati (Journal of English Education and Literature, 2025)
The purpose of this study was to determine the improvement of students' speaking by implementing self-talk strategy in the eleventh grade of SMKN 2 Mataram. In this study, researchers used Classroom Action Research by Kemmis and MC Taggart as a research design. This study was conducted in one cycle: planning, action, observation, and reflection. Data were analyzed using quantitative and qualitative approaches. The results of the study showed that the implementation of self-talk strategy was able to improve students' speaking skills in class XI MPK 1. This has been proven by the achievement of students' speaking tests seen from the comparison of pre-test scores of 14.47 and post-test scores of 18.97 where the pre-test score is smaller than the post-test score 14.47<18.97 or the post-test score is greater than the pre-test score 18.97>14.47. Not only on speaking scores, this strategy has also improved students' speaking skills in class XI MPK 1. This study contributes to the development of language teaching and learning strategies in schools or universities, especially in improving students' speaking skills. The findings of this study can be used as a reference for educators and teachers in developing effective language teaching methods. In addition, this study has implications for society, as it highlights the importance of self-confidence and self-expression in language learning, which can ultimately improve individuals' communication skills and their participation in social and professional contexts.